Pengaruh Budaya Organisasi dan Komitmen Organisasi Terhadap Kinerja Organisasi Pada PT Wijaya Karya Beton Tbk Kecamatan Sunggal Kabupaten Deli Serdang - Patrisyah, Gustia; Syahrial, Hery (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to determine the effect between organizational culture on organizational performance, and to determine the effect of organizational commitment on organizational performance in employees of PT Wijaya Karya Beton. This study uses a quantitative approach, with the type of associative research used to analyze the relationship or influence between two or more variables. The population in this study were 77 employees of PT Wijaya Karya Beton, with a sample of 75 employees selected using convinience sampling. Data collected using a questionnaire with a Likert scale of 1-5 distributed via google form to employees of PT Wijaya Karya Beton through HRD. Furthermore, the data obtained was analyzed using SEM-PLS Version 3.0. The results of the analysis show that there is a significant positive influence between organizational culture on organizational performance, as well as a positive and significant influence between organizational commitment on organizational performance. This research contributes to the integration of organizational culture and organizational commitment to organizational performance in one research framework which in previous studies to the knowledge of researchers has not been found. Furthermore, this study provides input to leaders about the importance of organizational culture and organizational commitment in improving organizational performance.